Evaluating the Efficacy of Ethical Guidelines for Online Screening of Mental Health in South Africa - Hassem, Tasneem; Laher, Sumaya (Frontiers in Psychology, 2022)
Despite the rapid growth in digital mental health options, a systematic review conducted on the ethics of developing online mental health screening instruments highlighted that there were no formal guidelines in this area. This lack of formal guidelines and the results of the systematic review resulted in the development of formal guidelines for placing a mental health screening tool online in South Africa. This study aimed to explore the efficacy of these draft guidelines using a qualitative design with two samples of individuals recognised as experts in the field of mental health. Sample one consisted of a purposive sample of 15 experts who commented on the appropriateness of the draft guidelines. The second sample consisted of 9 experts who completed the Appraisal of Guidelines for Research and Evaluation (AGREE) instrument to assess the efficacy of the guidelines. Both samples were in agreement on the relevance of the core content areas in the guidelines, namely purpose and scope, modes of testing, psychometric properties, informed consent, ensuring minimal risk to participants, feedback as well as data security. There was also agreement on the appropriateness of the methods used to develop the guidelines. The use of the guidelines was supported with the suggestion that issues of risk and suicidality be explored further.